Introduction to Buddhist Economics: The Relevance of Buddhist Values in Contemporary Economy and Society - Ng, Ernest C. H (Studies in Buddhist Economics, Management, and Policy, 2020)
1. What is Buddhist Economics? -- 2. The Four Noble Truths: A Decision-Making and Problem-Solving Framework -- 3. What is the Problem with the Market Economy? -- 4. Drivers behind the Shortcomings of the Market Economy -- 5. Buddhist Economics Theory -- 6. Buddhist Ethics and Moral Life -- 7. Buddhist Wisdom and Defining Principles -- 8. Interconnectedness, Competition, and Collaboration -- 9. Envisioning a Different "Growth Model" -- 10. Alternatives to Profit-Driven Economic Growth Models -- 11. Making Sustainable Decisions in Daily Life -- 12. Implications for Business, and for Social and Environmental Change.